Changes in physical activity behavior and C-reactive protein in breast cancer patients. Issue 7 (12th April 2018) - Sabiston, Catherine M; Wrosch, Carsten; Castonguay, Andrée L; Sylvester, Benjamin D
Abstract: Background: C-reactive protein (CRP) concentrations are associated with morbidity and mortality in breast cancer patients and moderate-vigorous physical activity (MVPA) may help regulate CRP levels. Purpose: The purpose of this prospective study was to examine intraindividual and interindividual changes in MVPA on changes in CRP levels among early posttreatment breast cancer patients. Methods: During five data collections over the first year posttreatment for breast cancer, women ( N = 138, M age = 55.3, standard deviation = 11.1 years) completed a questionnaire, wore an accelerometer for seven consecutive days to measure MVPA, and provided blood samples to measure CRP concentrations. Intraindividual and interindividual associations between MVPA on CRP were tested using hierarchical linear modeling. Results: Based on the intraindividual associations, lower concentrations of CRP were evident when participants engaged in more, as compared to their average, MVPA ( β = −.02, p < .021). In addition, interindividual analyses showed that women who engaged in more MVPA across the study period had lower concentrations of CRP compared to women who engaged in less MVPA ( β = −.24, p = .006). Conclusions: MVPA in breast cancer patients is consistently associated with lower CRP concentrations over time. Interventions may target individual MVPA early after diagnosis to mitigate CRP levels in breast cancer patients. Abstract : Increases in levels of physical activity are consistently associated with lower levels of C-reactive protein over time among breast cancer survivors